Linked arms : a rural community resists nuclear waste - Peterson, Thomas Virgil, 1943- (State University of New York Press, 2002)
"Through character development, snappy dialogue, and vivid scenes, Linked Arms tells the story of a rural people's successful struggle to keep a major nuclear dump out of Allegany County in western New York. Five times over a twelve-month period hundreds of ordinary people - merchants, homemakers, professionals, farmers, and blue collar workers - ignored potential jail terms and large fines to defy the nuclear industry and governmental authority by linking arms in the bitter cold to thwart the siting commission through civil disobedience."--Jacket